Faktor-faktor yang mempengaruhi pergantian auditor - ROBBY ADYTIA PUTRA; ITA TRISNAWATI (Jurnal Bisnis dan Akuntansi, 2016)
The objective of this research are to get empirical study that audit opinion, management changes, size KAP, percentage of changes in return on assets, financial distress, company growth, and public ownership have influence to auditor switch. This research used 120 non financial companies that met the criteria with total 360 data. Sample selected using purposive sampling method, during the research period 2011 until 2013. Hypothesis tested by using logistic regression analysis. The empirical results of this research show that audit opinion, management changes, size KAP, percentage of changes in return on assets, financial distress, company growth, and public ownership have no influence to auditor switch.